The moderating role of corporate sustainability practices on the relationship between board diversity and financial performance of firms in Malaysia - Molla, Mohammad Shahansha (2020)
Financial scandals and crises as well as the collapse of giant corporations globally have raised questions regarding the effectiveness of corporate governance mechanisms. Policymakers worldwide have attempted to tackle this issue by encouraging firms to diversify their board of directors. Previous studies showed that board diversity influenced financial performance. However, the relationship between board diversity and financial performance remains inconclusive due to firms‘ corporate sustainability practices. Thus, this study examined the relationship between board diversity and financial performance, corporate sustainability practices and financial performance, and the moderating role of corporate sustainability practices on the relationship between board diversity and financial performance. A sample of 104 firms listed on Bursa Malaysia from year 2015-17 was analyzed. Five types of board diversity were examined, namely, gender, ethnicity, age, education and outside directors which were measured by Blau‘s index while Tobin‘s Q was used as a proxy for financial performance. Content analysis was adopted to measure corporate sustainability practices considering the firm‘s economic, environmental and social activities. The study also employed three control variables, namely, board size, firm size, and leverage. Using panel corrected standard errors estimator model, this study showed that board diversity, as well as corporate sustainability practices significantly and positively affected financial performance. Furthermore, results from the hierarchical moderated multiple regression model revealed that corporate sustainability practices significantly moderated the relationship between board diversity and financial performance. The main contribution of this study is that corporate sustainability practices, as a moderator, has a strong effect on the relationship between board diversity and financial performance. Thus, the government and regulatory bodies should ensure that firms diversify their board of directors. Also make corporate sustainability practices mandatory to enhance financial performance for their long-term survival and to reduce the risk of collapse.